Future Armenia : Connect, Compete, Prosper - World Bank Group (World Bank, Washington, DC, 2018)
Since its independence in 1991 and until prior to the global financial crisis (GFC) in 2008-09, Armenia was considered an important success story among the transition economies. Indeed, over several years, the country displayed a record of sustained macroeconomic achievements, reflected in high growth, economic stability, low inflation, and modest deficits and external debt, as well as falling poverty rates and shrinking income disparities. This Systematic Country Diagnostic (SCD) identifies four challenges for Armenia to reinvigorate inclusive growth and resilience. First, with far less supportive external circumstances, reigniting economic growth calls for asearch for new drivers and the rebalancing of growth toward the tradable sectors. Against this backdrop, the country’s low export performance and limited global multi-connectivity caused by high trade and transport facilitation costs are the first challenges to be addressed. Second, insufficient private sector productivity stands in the way of both higher growth and job creation. Firms, as the productive engines of the economy, appear constrained in their ability to lift productivity reforms, limited competition, and the need to deepen further financial development. Third, poverty reduction and shared prosperity, that is, the transmission of aggregate growth to individual wellbeing and poverty reduction, also seems constrained by labor market challenges: labor resources are shrinking, labor-force participation is low, and the country has one of the lowest employment and highest unemployment rates in the Europe and Central Asia (ECA) region, whileworkers’ productivity has fallen. Learning outcomes seem to lag demand, both in terms of the level and type of skills that are sought by the market. Declining labor resources are compounded by low women participation in the labor market. Fourth, key vulnerabilities at the macroeconomic, environmental, and microeconomic levels are faced by Armenia in its quest for poverty reduction and shared prosperity. Armenia’s aging population will have a significant impact on health spending and on the pension system, and could, if not addressed, have major implications in terms of fiscal sustainability and poverty.